Contemporary accounting : a conceptual approach - Jarvis, Robin.; Bazley, Mike.; Hancock, Phil.; Berry, Aidan. (Nelson ITP, 1999)
This book is about: Introduction to accounting; The conceptual framework; The balance sheet; ...